Relationship between the Rate of Perceived Stability, electrodermal activity and task performance during balance challenges in chronic stroke - Aishwarya Shenoy; Amy Schneeberg; Towela Tembo; Rebecca M. Todd; Noah D. Silverberg; Janice J. Eng; Tzu-Hsuan Peng; Peyman Servati; Courtney L. Pollock (PLoS ONE, 2026)
Introduction In addition to sensorimotor impairments following stroke, decreased self-efficacy regarding walking balance may lead to self-imposed limitations on community level mobility, especially among women. The Rate of Perceived Stability (RPS) is a self-efficacy measure used to assess individual perception of balance ability when standing or walking balance is challenged. Measurement of electrodermal activation (EDA), modulated by the autonomic nervous system, during perturbations to standing balance reflects the physiological arousal (‘fight or flight’) response of the individual as they maintain or recover their balance. Repeat performance of a balance task has been shown to result in habituation of EDA within a single session; however, studies have yet to test whether similar habituation occurs when the same balance tasks are repeated across different days. This study aims to examine the relationships between EDA, task performance ability, and RPS in individuals with chronic stroke performing walking balance challenges. Further, the study explores how sex and repeat exposure (repeat performance of task) moderate these relationships. Methods Over two testing days, participants with chronic stroke (>1 year) were assessed on walking balance task performance with the Community Balance and Mobility Scale (CB&M) and rated their perceived stability using the RPS. EDA measured the physiological arousal during task performance. Linear mixed models were used to assess: 1) the relationship between CB&M task performance and RPS and whether sex or repeat exposure moderates this relationship, 2) the relationship between the physiological arousal response and RPS and whether sex or repeat exposure moderates this relationship, and 3) whether physiological arousal response mediates the relationship between CB&M task performance and RPS. Results Thirty individuals with chronic stroke, with moderate severity lower extremity impairment (Chedoke McMaster Stroke Assessment score 4–5/7) participated in the study, including 15 males (mean age: 65.1 ± 10.2 years; time since stroke: 9.4 ± 4.7 years) and 15 females (mean age: 65.5 ± 9.7 years; time since stroke: 7.6 ± 5.9 years). CB&M scores, indicating balance performance, explained 20.3% of the variability in the RPS. As CB&M task performance improved, RPS scores decreased by 2.69 (95% CI [−3.28 – −2.10]) to 3.67 (95% CI [−4.32 – −3.02]) points, indicating improved perceived stability. Physiological arousal significantly predicted RPS scores, however only explained 1.6% of the variability in the RPS. Physiological arousal was not found to be a significant mediator of the relationship between the CB&M task performance scores and RPS. Participant-specific random effects accounted for more variance in the RPS than the fixed effects of task performance and physiological arousal, explaining 46% of variance in RPS. Repeat exposure and sex did not moderate the relationships between the predictors (physiological arousal and task performance) and RPS. Conclusion Ability to perform a walking balance task (CB&M task performance score) and the underlying physiological arousal response (EDA) are independent predictors of perception of balance in people with chronic stroke as measured by the RPS. However, individual characteristics not captured in this study account for a greater proportion of the variability of the self-reported perception of balance during tasks performed. Potential characteristics may include constructs such as fall history and level of physical activity highlighting the complexity of perception of balance ability post-stroke.